2011
DOI: 10.1177/1741826710389390
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen uptake efficiency slope in children with congenital heart disease: construct and group validity

Abstract: The OUES provides a valid measure of cardiopulmonary fitness in children with CHD, which is independent of exercise intensity and strongly correlated with VO(2peak) and VT (construct validity). Furthermore, the OUES is capable of differentiating between healthy children and children with CHD and between Fontan and ToF patients (group validity). Therefore, the OUES may be a valid, effort-independent parameter of cardiopulmonary fitness in children with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 49 publications
9
32
2
1
Order By: Relevance
“…Most studies found no significant differences between maximal and submaximal oxygen uptake efficiency slope values [19,21,22,24,25,28], whereas other studies reported small differences [14,18,20,26]. Most studies found no significant differences between maximal and submaximal oxygen uptake efficiency slope values [19,21,22,24,25,28], whereas other studies reported small differences [14,18,20,26].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Most studies found no significant differences between maximal and submaximal oxygen uptake efficiency slope values [19,21,22,24,25,28], whereas other studies reported small differences [14,18,20,26]. Most studies found no significant differences between maximal and submaximal oxygen uptake efficiency slope values [19,21,22,24,25,28], whereas other studies reported small differences [14,18,20,26].…”
Section: Discussionmentioning
confidence: 96%
“…Figure 3 Receiver operator curves for predicting a peak oxygen uptake ≤ 18.2 ml.kg À1 .min À1 (left graph) and a ventilatory anaerobic threshold ≤ 11.1 ml.kg À1 .min À1 (right graph) from the oxygen uptake efficiency slope normalised for body mass calculated using all exercise data ( ), 90% of the data ( ) and 80% of the data ( ). 14, [18][19][20][21][22][23][24][25][26][27][28][29][30] and indicates that the oxygen uptake efficiency slope is an objective measure of cardiorespiratory fitness. The two patients (both men, 72.3 and 75.9 years of age) who had a difference of > 200 between OUES100 and OUES80 values, demonstrated a consistent levelling-off of oxygen uptake during the last part of the cardiopulmonary exercise test, without showing a clear oxygen uptake plateau (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have assessed the validity of the OUES in clinical populations, such as congestive heart failure and congenital heart disease, finding it, to an extent, to be a suitable, effort‐independent, parameter of aerobic fitness. Moreover, two previous studies have assessed the applicability of the OUES in individuals with CF.…”
Section: Discussionmentioning
confidence: 99%